Lipopolysaccharide-Activated Canine Platelets Upregulate High Mobility Group Box-1 via Toll-Like Receptor 4 - Li, Ronald H. L.; Hommel, Caelin; Nguyen, Nghi (Frontiers in Veterinary Science, 2021)
High mobility group box-1 (HMGB1) and the toll-like receptor 4 (TLR4) axis are key mediators of inflammation. Platelet-derived high mobility group box-1 (HMGB1) may also play a critical role in sepsis-mediated thrombosis resulting in complications like disseminated intravascular coagulation and multiple organ failure. While elevated levels of HMGB1 have been documented in humans and dogs with systemic inflammatory response syndrome and sepsis, a better understanding of how platelet agonists and lipopolysaccharide (LPS) mediate platelet HMGB1 expression would open doors to novel therapies for sepsis-mediated thrombosis. Herein, we sought to determine if canine platelets express HGMB1 in the presence or absence of LPS and agonists (ADP or thrombin) and if surface expression of HMGB1 is dependent on platelet TLR4. Canine platelets were unstimulated (resting) or activated with thrombin or adenosine diphosphate (ADP) in the presence or absence of E. coli LPS prior to flow cytometric and western blot analyses for TLR4 expression. We also treated canine platelets with or without TLR4 function blocking antibody or its isotype control. We discovered that while thrombin upregulated both surface and cellular HMGB1 expression, LPS-mediated activation in the presence of ADP priming led to upregulation of surface HMGB1 expression. This expression was found to be most prominent in platelets that had undergone alpha-granule secretion. Inhibition of TLR4 attenuated LPS-induced HMGB1 expression indicating that exteriorization of HMGB1 may be dependent on the non-genomic pathway of platelet TLR4. Our findings indicate that upregulation of platelet-derived HMGB1 as a result of thrombin or TLR4-mediated activation may contribute to hypercoagulability in clinical septic dogs. Future studies should explore the translational implication of platelet-derived HMGB1 as novel therapeutic targets in humans and dogs with sepsis.